Scientific Guidance on the criteria for the evaluation and on the preparation of applications for the safety assessment of post‐consumer mechanical PET recycling processes intended to be used for manufacture of materials and articles in contact with food - EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP); Claude Lambré; José Manuel Barat Baviera; Claudia Bolognesi; Andrew Chesson; Pier Sandro Cocconcelli; Riccardo Crebelli; David Michael Gott; Konrad Grob; Marcel Mengelers; Alicja Mortensen; Gilles Rivière; et al. (EFSA Journal, 2024)
Abstract In the context of entry into force of Regulation (EU) 2022/1616, EFSA updated the scientific guidance to assist applicants in the preparation of applications for the authorisation or for the modification of an existing authorisation of a ‘post‐consumer mechanical PET’ recycling process (as defined in Annex I of Regulation (EU) 2022/1616) intended to be used for manufacturing materials and articles intended to come into contact with food. This Guidance describes the evaluation criteria and the scientific evaluation approach that EFSA will apply to assess the decontamination capability of recycling processes, as well as the information required to be included in an application dossier. The principle of the scientific evaluation approach is to apply the decontamination efficiency of a recycling process, obtained from a challenge test with surrogate contaminants, to a reference contamination level for post‐consumer PET, set at 3 mg/kg PET for a contaminant resulting from possible misuse. The resulting residual concentration of each surrogate in recycled PET is then compared to a modelled concentration in PET that is calculated using generally recognised conservative migration models, such that the related migration does not give rise to a dietary exposure exceeding 0.0025 μg/kg body weight (bw) per day. This is the lowest threshold for toxicological concern (TTC) value, i.e. for potential genotoxicity, below which the risk to human health would be negligible. The information to be provided in the applications relates to: the recycling process (i.e. collection and pre‐processing of the input, decontamination process, post‐processing and intended use); the determination of the decontamination efficiency by the challenge test; the self‐evaluation of the recycling process. On the basis of the submitted data, EFSA will assess the safety of the mechanical PET recycling process.